Nekatere izgubljene priložnosti novih zakonov - Prelovšek, Andrej (Urbani izziv, 2003)
The article presents constructive reflections about some deficiencies of the recently adopted laws on spatial management and building. The critique mainly deals with inconsistent enforcement of the concept of deregulation, contents of planning documents, mechanisms of motivation, aspiration and profit, as well as neglect of initiative, the motor of spatial management. Poor communication and lack of mechanisms for achieving better architecture and spatial order are emphasised.
Keywords: civil engineering; gradbeništvo; pravna ureditev; prostorsko planiranje; prostorsko urejanje; spatial planning; statute; urejanje prostora; zakoni